The Effect of Green Manure from Turi Plants (Sesbania grandiflora) on the Growth and Yield of Yardlong Bean (Vigna sinensis L.) Variety Guarda - Muhammad Zidan Cipta Raihan; Bakhrully Bintang Ramadhan; Achmad Faqih (International Journal of Social Service and Research, 2026)
This research aimed to determine the effect of green manure derived from turi (Sesbania grandiflora) on the growth and yield of yardlong bean (Vigna sinensis L.) cultivar Guarda, as well as to identify the most effective application rate. The research was conducted from November to January 2026 in Cibunar, Tegal Regency, using a single-factor Randomized Complete Block Design with five levels of green manure application: 5, 10, 15, and 20 tons/ha, and 10.8 kg per plant. Each treatment was replicated five times, resulting in a total of 25 experimental units. The observed parameters (plant height, number of leaves, stem diameter, leaf area, pod weight per plant, and pod weight per plot), were analyzed using ANOVA followed by Duncan’s Multiple Range Test. The results showed that turi green manure had no significant effect on plant height, number of leaves, stem diameter, and pod weight per plant at various observation times. However, a significant effect was observed on leaf width at 21 days after planting, where the application rate of 15 tons/ha produced wider leaves compared to other treatments, potentially enhancing photosynthetic efficiency. In addition, pod weight per plot differed significantly at 45 and 49 days after planting, with the control treatment (0 tons/ha) producing the highest yield at the first harvest (45 days), while the 5 tons/ha treatment showed the best result at 49 days. Overall, turi green manure provided limited benefits, with the optimal application rate ranging from 5 to 15 tons/ha depending on the growth stage and observed parameters.